Massive Pulmonary Thromboembolism Demonstrated at Necropsy in Japanese Psychiatric Patients Treated With Neuroleptics Including Atypical Antipsychotics - Hamanaka, Satoko; Nagai, Tomonori; Miyaoka, Hitoshi; Kurihara, Katsuyoshi; Kamijo, Yoshito; Soma, Kazui; Tanaka, Katsutoshi (Circulation Journal, 2004)
Background There may be an increased risk of pulmonary thromboembolism (PTE) with antipsychotic drugs, so this association was investigated in autopsy cases of sudden unexpected death determined by the Department of Legal Medicine of a Japanese university hospital. Methods and Results Records of 1,125 forensic autopsies (808 males, 317 females) performed during the study period for investigation of the cause of sudden unexpected death were reviewed and a logistic regression analysis was performed to explore whether age, gender, body mass index (BMI), and antipsychotic drug use were associated with fatal PTE. Among all records, 34 (3.0%; 14 males, 20 females) indicated the use of antipsychotic drugs and 28 (2.5%; 9 males, 19 females) indicated PTE as the cause of death. Of the 28 subjects who died from PTE, 8 had taken antipsychotic drugs (29%) and all were female. Female gender and antipsychotic drug use accounted for a significantly higher risk of PTE death with an odds ratio of 4.22 (95% confidence interval (CI), 1.82-9.78; p<0.01) and 10.49 (95% CI, 3.95-27.85; p<0.01), respectively. Conclusions Japanese women taking antipsychotic drugs may be at particular risk for PTE. (Circ J 2004; 68: 850 - 852)